Konstipasi Fungsional pada Anak - Muzal Kadim (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2021)
Constipation has a negative impact, both for the child and their family, because it can reduce the quality of life, as well as impact on health care costs. The diagnosis of functional constipation is based on Rome IV criteria. The prevalence of functional constipation is related to geography, dietary habits and types, and exposure to stressful life events for children. Although most constipation in children is functional, an organic disorder must be excluded by looking for any alarm signs.